Pet Loss and Representations of Death, Attachment, Depression, and Euthanasia. (2nd January 2017) - Testoni, Ines; De Cataldo, Loriana; Ronconi, Lucia; Zamperini, Adriano
ABSTRACT: Studies that have examined pet loss hypothesize that attachment, representations of death, and the belief in an afterlife for animals may influence owners' bereavement and depressive outcomes. The following instruments were administered to 159 Italian participants recruited through snowball sampling: the Lexington Attachment to Pets Scale (LAPS), the Pet Bereavement Questionnaire (PBQ), the Testoni Death Representation Scale (TDRS), and Beck's Depression Inventory II (BDI-II). Questions concerning pet euthanasia-related issues and the relationship between owners and veterinarians were also submitted to the participants. A path model was conducted, showing that the representation of death and the attachment to a pet had a direct effect on pet grief, which in turn had a direct effect on depression. The results show a positive correlation between the LAPS and PBQ factors, particularly with the PBQ factor Grief. The LAPS factors positively correlated with the TDRS representation of Death as a Passage and negatively correlated with the TDRS representation of Death as Annihilation. The LAPS People Substituting factor positively correlated with the total score and the Cognitive-Affective factor of the BDI-II. The PBQ factors positively correlated with the BDI-II, whereas only the TDRS Death as Annihilation factor positively correlated with the BDI-II. Belief in a transcendent dimension was associated with higher scores on the PBQ Guilt factor and the TDRS factors of Death as a Passage and Death as Change, whereas these beliefs were associated with lower scores on the TDRS factor Death as Annihilation. The results indicated that the sensitivity of the veterinarian and a veterinarian who helps owners make conscious and informed decisions for their pet and choose the right time to perform euthanasia are important variables in the management of pet loss. However, these factors are not sufficient and psychological support should be improved to help owners better cope with grief.